PENGARUH METODE BERCERITA DENGAN MAKET TERHADAP KECERDASAN VISUAL SPASIAL PADA ANAK USIA 5-6 TAHUN DI TK INAYAH PEKANBARU - Detri Anisa; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of story telling method with maket towards spatial visual intelligence of children aged 5-6 years in TK Inayah Pekanbaru. The method of this research used experimental method with using one group pre-test post-test design. The samples used in this study were 18 students. The data collection technique used is observation. Technique of data analysis used t-test by using program of SPSS 17. The research hypothesis was to find the influence of story telling method with maket towards spatial visual intelligence of children aged 5-6 years in TK Inayah Pekanbaru. Based on data analysis was known that tcalculated = 26.913>ttable = 2.110 with Sig. (2-tailed) = 0.000. Because Sig <0.05 it can be concluded that there is difference of spatial visual intelligence that was be done before and after of story telling method with maket. It can be interpreted that there is influence of story telling method with maket activity towards spatial visual intelligence of children aged 5-6 years in TK Inayah Pekanbaru significant that is equal to 62.14%. Keyword: Spatial Visual Intelligence, Story Telling Method With Maket